Evaluation of Multicomponent Measuring Instrument Reliability in Complex Design Studies. Issue 2 (3rd March 2016) - Raykov, Tenko; Traynor, Anne
Abstract : A latent variable modeling approach to evaluation of scale reliability in complex design studies is outlined. The procedure is readily applicable in empirical research for the purpose of point and interval estimation of reliability of multicomponent measuring instruments in the presence of probability sampling and possible nesting within higher order units. The method can be used to aid scale construction and development efforts in large-scale studies of substantially heterogeneous populations. The described approach is illustrated with data from an international educational survey.